2007
DOI: 10.1111/j.1532-950x.2007.00274.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 9 mm Tibial Tuberosity Advancement on Cranial Tibial Translation in the Canine Cranial Cruciate Ligament‐Deficient Stifle

Abstract: Objective-To assess the effect of 9 mm tibial tuberosity advancement (TTA) on cranial tibial translation (CTT) in cranial cruciate ligament (CCL) deficient canine stifles.Study Design-In vitro cadaveric study. Animals-Twelve canine pelvic limbs.Methods-Each stifle was placed in a jig at 135° with a simulated quadriceps force and tibial axial force, and the distance of CTT was measured with the CCL intact (iCCL), transected (tCCL), and after performing a TTA using a 9 mm cage. In addition, a material testing ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 112 publications
3
59
0
Order By: Relevance
“…This residual instability is attributed to the character of the study using cadavers. The cranial tibial thrust force is minimized by the balance between the quadriceps muscle group and the flexor mechanism, and the stability is dependent upon the full action of these muscles during locomotion (FALCIS et al, 2006;HOFFMANN et al, 2006;MILLER et al, 2007). Dog 3 had an excessive tibial subluxation of 7mm attributed to a sloped tibial plateau of 28° (VEZZONI, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This residual instability is attributed to the character of the study using cadavers. The cranial tibial thrust force is minimized by the balance between the quadriceps muscle group and the flexor mechanism, and the stability is dependent upon the full action of these muscles during locomotion (FALCIS et al, 2006;HOFFMANN et al, 2006;MILLER et al, 2007). Dog 3 had an excessive tibial subluxation of 7mm attributed to a sloped tibial plateau of 28° (VEZZONI, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…According to some authors, the magnitude of transformation of the cranial tibial thrust force is directly proportional to the amount of cranial displacement of the tibial tuberosity (APELT et al, 2007). This observation highlights the necessity for other studies to determine the ideal distance for tibial tuberosity advancement and the effects of excessive reduction on caudal cruciate ligament and other joint components (REIF et al 2002;TEPIC, 2006;MILLER et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite overall acceptance by most surgeons, studies using force plate analysis showed similar results in long-term outcome for the lateral suture technique and the Slocum TPLO (CONZEMIUS et al, 2005). Tibial Tuberosity Advancement (TTA) was described as a new alternative for stabilizing the cranial cruciate deficient stifle (MILLER et al, 2007). According to the authors, the method promotes less alteration to the intraarticular and periarticular components, and therefore leads to superior clinical results (TEPIC, 2006).…”
Section: Introductionmentioning
confidence: 99%